Given:
A.)
Slope of the line (m) = -2/3
Y-intercept (b) = 3
The given can be used to make an equation under the Slope-Intercept Form:
![\text{ y = mx + b}](https://img.qammunity.org/2023/formulas/mathematics/college/jktsxg4fkjzyla0fu188v2p7nlvte8hjri.png)
By substituting m and b to y = mx + b, we can generate the equation.
We get,
![\text{ y = mx + b}](https://img.qammunity.org/2023/formulas/mathematics/college/jktsxg4fkjzyla0fu188v2p7nlvte8hjri.png)
![\text{ y = (-2/3)x + (3)}](https://img.qammunity.org/2023/formulas/mathematics/college/23enqobrfq1rwcc6b3ifiaeq37ct2n84wp.png)
![\text{ y = -}(2)/(3)x\text{ + 3}](https://img.qammunity.org/2023/formulas/mathematics/college/8cxvpvf2ddp2feu7b4dplcy1umy64fxais.png)
![3(\text{ y = -}(2)/(3)x\text{ + 3)}](https://img.qammunity.org/2023/formulas/mathematics/college/kg87666at28tdzzu8ln5banc8vqfgn85is.png)
![3y\text{ = -2x + 9}](https://img.qammunity.org/2023/formulas/mathematics/college/4n8in7i9xb0kfp7d8tmircajhjcgpuurz9.png)
![2x\text{ + 3y = 9}](https://img.qammunity.org/2023/formulas/mathematics/college/922jxmnaft4zuz74bg5ngzhn2cvmzygx5z.png)
Therefore, the equation match to m = -2/3 and b = 3 is 2x + 3y = 9.
B.)
Slope of the line (m) = -3/2
x,y = 4,-1
To be able to generate the equation, let's first determine the y-intercept (b). We can get it by substituting m = -3/2 and x,y = 4,-1 to the equation y = mx + b.
We get,
![\text{ y = mx + b}](https://img.qammunity.org/2023/formulas/mathematics/college/jktsxg4fkjzyla0fu188v2p7nlvte8hjri.png)
![\text{ -1= (-3/2)(4) + b}](https://img.qammunity.org/2023/formulas/mathematics/college/mvku1csizxqg9p6efb83h7zm5ganq259ag.png)
![-1\text{ = }(-12)/(2)\text{ + b }\rightarrow\text{ -1 = -6 + b}](https://img.qammunity.org/2023/formulas/mathematics/college/au5vvr5h44tlfuylms1sxlm44ofmc6hs34.png)
![\text{ b = -1 + 6}](https://img.qammunity.org/2023/formulas/mathematics/college/wl9fcbdcje0m2frcxqk6zngwtkvahkdk7u.png)
![\text{ b = 5}](https://img.qammunity.org/2023/formulas/mathematics/college/j6skf3atdn4d97i51bav5d34lmdnhs9vxw.png)
Since we now found that the y-intercept (b) = 5, let's substitute b and m = -3/2 to y = mx + b to generate the equation.
We get,
![\text{ y = mx + b}](https://img.qammunity.org/2023/formulas/mathematics/college/jktsxg4fkjzyla0fu188v2p7nlvte8hjri.png)
![\text{ y = (-3/2)x + (5)}](https://img.qammunity.org/2023/formulas/mathematics/college/e7powt5k7b1t53ombc6k91d1g30pid4q60.png)
![\text{ y = -}(3)/(2)x\text{ + 5}](https://img.qammunity.org/2023/formulas/mathematics/college/ikjo4lf7hnc1jwb2rwqytpaovg9apn95n4.png)
![\text{ -2(y = -}(3)/(2)x\text{ + 5)}](https://img.qammunity.org/2023/formulas/mathematics/college/r23cigs3ffycmcnkqzvmu7kwyk0nlpdy4o.png)
![\text{ -2y = 3x - 10}](https://img.qammunity.org/2023/formulas/mathematics/college/m4l95hsnmxyfepwxpbunnp3fxravzax578.png)
Therefore, the equation that match m = -3/2 and (4,-1) is -2y = 3x - 10.